Pengaruh Penggunaan Teknik Blow Torch Terhadap Kadar Air Pada Pembuatan Lemang Di Kab. Lahat - Marna Sonjaya, Arief (Politeknik Pariwisata Medan, 2024)
this study aims to determine the effect of blow torch technique on lemang processing in Lahat district. In addition, this research was also carried out to design and compile culinary gastronomic innovations in lemang in order to find solutions for cooking and shelf-life of lemang so that they can be used as souvenirs for tourists. The research method used is a descriptive method to explain the history of lemang processing in Lahat Regency, and an experimental method with a quantitative approach is used to determine the effect of the Blow Torch Technique on making lemang on the amount of lemang water content which can affect the shelf life of lemang. Designing lemang gastronomic innovations using Torch technique at the end of the lemang. The data used in this study are primary data and secondary data obtained by observation and experimentation through several stages of research. The lemang in Lahat is processed traditionally, so it has the disadvantage of a long cooking time and a short shelf life, so an innovation made to lemang is the use of the Blow Torch Technique in making lemang to reduce the water content of the ends of the lemang so as to produce longer resistance to lemang. , ie up to five days at room temperature